Metabolomics profiling of steatosis progression in HepaRG® cells using sodium valproate. (April 2018) - Cuykx, Matthias; Claes, Leen; Rodrigues, Robim M.; Vanhaecke, Tamara; Covaci, Adrian
Graphical abstract: Highlights: Design of experiment is important in untargeted metabolomics research. Valproic acid invokes a typical steatosis progression in HepaRG cells. Adaptive responses include spermidine alteration and an upregulation of SAMe. New potential biomarkers include acetylcholine, creatine and spermidines. Abstract: Non-alcoholic Fatty Liver Disease (NAFLD) is a frequently encountered Drug-Induced Liver Injury (DILI). Although this stage of the disease is reversible, it can lead to irreversible damage provoked by non-alcoholic steatohepatitis (NASH), fibrosis and cirrhosis. Therefore, the assessment of NAFLD is a paramount objective in toxicological screenings of new drug candidates. In this study, a metabolomic fingerprint of NAFLD induced in HepaRG ® cells at four dosing schemes by a reference toxicant, sodium valproate (NaVPA), was obtained using liquid-liquid extraction followed by liquid chromatography and accurate mass–mass spectrometry (LC–AM/MS). The combination of a strict design of experiment with a robust detection method, applied on sodium valproate, validated the possibilities of untargeted metabolomics in hepatic toxicological research. Distinctive patterns between exposed and control cells were consistently observed, multivariate analyses selected up to 200 features of interest, revealing hallmark NAFLD-biomarkers, such as diacylglycerol and triglyceride accumulation and carnitine deficiency. Initial toxic responses show increased levels of S -adenosylmethionine and mono-acetylspermidine in combination with only a moderate increase in triglycerides. New specific markers of toxicity have been observed, such as spermidines, creatine, and acetylcholine. The described design of experiment provides a valuable metabolomics platform for mechanistic research of toxicological hazards and identified new markers for steatotic progression.